CORRELATION BETWEEN ORGANIZATION CULTURE WITH ORGANIZATION COMMITMENT ON EMPLOYEE AT PT. YODYA KARYA (PERSERO) JAKATA TIMUR - Muhammad Rahmansyah; Umi Widyastuti; Darma Rika Swaramarinda (Jurnal Ilmiah Econosains, 2015)
ABSTRACTThe purpose of this research is to detect correlation between organization culture with organization commitment on Employee at PT. Yodya Karya. The research is done during for two months since May until June 2014. The method of research is survey method with correlation approach. The population research was employee in PT. Yodya Karya center board with total 57 employee, and 48 employees for sampling and usedprobability random sampling. Instrument that used to get variable data X (Organization Culture) and variable data Y measured by questionnaire using Likert scale. The analysis test by finding regression equation, that is Å¶ = 45,47 + 0,29X. Analysis rules test that is test normalitas while analysis rules test that is test normalitas regression estimation error Y on X with test Liliefors got Lhitung (0,1202) < Ltabel (0,1278) matters this means sample comes from population normal distribution. Significancy test and regression linearity by using analysis table varians (Anava) got regression similiarity Fhitung (8,67) > Ftabel (4,05) that declare regression very mean with regression linearity test that produce Fhitung (0,91) < Ftabel (2,04) that show the regression model that used linear. Correlation coefficient hypothesis test is done with formula product moment produce rhitung = 0,401. Significancy test with thitung (2,97) > ttabel (1,68). Because thitung > ttabel, from watchfullness result so researcher can conclude that found connection significant between organization culture with organization commitment on employee PT. Yodya Karya. Determination coeficient test produce KD as big as 16,1%. So can be taken conclusion found which are positive connection and significant between organization culture and organization commitment.Keywords : Organization Culture, Organization Commitment